Pengaruh Pengelolaan Kelas Terhadap Motivasi Belajar Siswa Kelas IV Madrasah Ibtidaiyah Salman Dompu - Nuryanti; Mulya Yusnarti (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2025)
This research aimed to determine the effect of classroom management on student learning motivation. The research population was all fifth grade elementary school students, totaling 15 students who were selected using purposive sampling. The data collection techniques used in this research were questionnaires, observation, interviews, documentation. The type of research used in this research is descriptive research method using a quantitative approach. Based on the research results, it can be concluded that there is an influence of classroom management on the learning motivation of class IV students at Madrasah Ibtidaiyah Salman Dompu, with the Rtable test results obtained for the validity test, namely 0.413, which is greater than the Rcount. Meanwhile, through the Cronbach's Alpa reliability test, each variable showed a Cronbach Alpa result of >0.6, namely the reliability of class management statistics was 0.934 and the reliability of student learning motivation was 0.933. And the t test via the coefficient of significance on the variable shows a significance of 0.000<0.005 so it can be concluded that Ha is accepted and Ho is rejected. This means that the better the classroom management, the higher the student's learning motivation. Likewise, viceversa, the less classroom management, the lower the students' learning motivation